Identifikasi Karakter Morfologi Mangga (Mangifera Indica L.) di Kecamatan Panyileukan, Jawa Barat, Indonesia - Fajar Ramadhan; Muhammad Mubiar Ramadana; Mutia Ramadhina Hastin; Ateng Supriatna (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
Mango (Mangifera indica L.) is a fruit that is loved by people all over the world. This research aims to determine the morphological characteristics of mango fruit in Panyileukan District, West Java, Indonesia. This research was conducted in four villages, namely Mekar Mulya, Cipadung Kidul, Cipadung Wetan and Cipadung Kulon. This research aims to determine the morphological characters of mangoes in Panyileukan District. Field data collection was carried out by observing the mango varieties planted by the community in their home gardens. A total of eight varieties of mango were found at the research location: mango gedong, garifta, arumanis, cengkir, kaweni, grogot, simanalagi and apple. Each mango variety has different morphological characteristics. Botanical identification was carried out by comparing the morphological characteristics of mango trees using several publications, including journals, magazines and websites. There were 8 types of mango, namely; gedong, garifta, arumanis, cengkir, keweni, grogot, simanalagi and apple